A possible mechanism of motor blockade of high volume pericapsular nerve group (PENG) block: A cadaveric study - Çiftçi, Bahadır; Ahıskalıoğlu, Ali; Altıntaş, Hilal Melis; Tekin, Bahar; Şakul, Bayram Ufuk; Alıcı, Hacı Ahmet (Elsevier Inc., 2021)
To the Editor, Pericapsular nerve group (PENG) block is an interfascial plane block that provides analgesia for the hip. PENG block targets the hip capsule by blocking the articular branches of the femoral nerve (FN) and the accessory obturator nerve (AON). The local anesthetic is administrated below the psoas muscle-tendon between the anterior inferior iliac spine (AIIS) and iliopubic eminence (IPE) [1]. After its first description for hip fracture analgesia, PENG block has been reported to provide analgesia for several indications such as varicose vein surgery, intertrochanteric femur fracture, prevention of adductor muscle spasm, and mass excision of the medial thigh [2–6]. Giron-Arango et al. emphasized that the main advantage of the PENG block is the motor-sparing effect because of blocking only the articular branches of FN and AON that have only sensory fibers [1,6]. There are clinical reports about motor weakness after PENG block in the literature. Yu et al. performed PENG block and reported inadvertent quadriceps weakness after the block with 20 ml [7]. Ahiskalioglu et al. performed PENG block with 30 ml LA in two patients and reported quadriceps weakness in one of them [3]. There-fore, the mechanism of motor weakness and spread of LA during PENG is still unclear. Several questions come to mind: can the high volume PENG block cause motor weakness, and can the high volume PENG block act like a lumbar plexus block? In light of these points, in this cadaveric study, we aimed to evaluate the spread of LA following PENG block with 20 ml or 30 of dye.
Keywords: Motor Blockade; Pericapsular Nerve Group (PENG); A Cadaveric Study